2017
DOI: 10.1186/s12936-017-2069-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of G6PD Mediterranean in individuals with and without malaria in Southern Pakistan

Abstract: BackgroundPakistan has an estimated annual burden of 1.5 million malaria cases. The current situation calls for an effective malaria control and eradication programme in this country. Currently, primaquine is an attractive option for eliminating reservoirs of Plasmodium vivax hypnozoites and killing gametocytes of Plasmodium falciparum. However, this drug causes haemolysis in individuals who are glucose-6-phosphate (G6PD) deficient. It is important to map G6PD deficiency and malaria distribution in Pakistan to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Though vivax malaria is endemic and seen throughout the year in most places, an alarming high prevalence was noted in falciparum malaria for many provinces in Pakistan [12]. Our previous work showed the presence of G6PD de ciency in a malaria-endemic region [13] while blood type O was reported as the most frequent (ranging from 28.8% to 35.5%) ABO type in the country [14][15][16]. Despite, these facts, no local data is available for ABO-allelic frequency.…”
Section: Introductionmentioning
confidence: 82%
“…Though vivax malaria is endemic and seen throughout the year in most places, an alarming high prevalence was noted in falciparum malaria for many provinces in Pakistan [12]. Our previous work showed the presence of G6PD de ciency in a malaria-endemic region [13] while blood type O was reported as the most frequent (ranging from 28.8% to 35.5%) ABO type in the country [14][15][16]. Despite, these facts, no local data is available for ABO-allelic frequency.…”
Section: Introductionmentioning
confidence: 82%
“…In Pakistan Primaquine administration needs mandatory G6PD testing although this test is not widely available. A study from the southern Pakistan showed that out of 200 participants 6 were G6PD deficient [22]. Recurrent jaundice due to hemolytic anemia can occur in G6PD deficient people.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Study in Southern Pakistan was done to evaluate the frequency of G6PD Mediterraneanin male individuals with and without falciparum malaria. [ 29 ] G6PD-Mediterranean is one variant characterized by severe enzyme deficiency and B-like electrophoretic mobility. [ 30 ] Though frequency for this G6PD allele was different in malaria-patients in comparison with healthy individuals they concluded that there is a need of large studies including females to find out true burden of G6PD in malaria-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Though frequency for this G6PD allele was different in malaria-patients in comparison with healthy individuals they concluded that there is a need of large studies including females to find out true burden of G6PD in malaria-endemic areas. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%